KONDISI SOSIAL EKONOMI MASYARAKAT NELAYAN DI DESA KUALA TERUSAN PASCA TERBENTUKNYA PEMERINTAHAN KABUPATEN PELALAWAN - Hutapea, Riyanda; Ibrahim, Bedriati; Fikri, Asyrul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Kuala Terusan village is located on the banks of the Kampar river, Pangkalan Kerinci sub-district, Pelalawan district and is inhabited by 115 families who work as traditional fishermen as the main income with simple fishing gear, so their economic level is still below the poverty line. The number of health and education facilities is also a factor in changing the village economy. The research objectives: (1) To determine the educational condition of the fishing community after the formation of the Pelalawan Regency government. (2) This is to determine the health condition of the fishermen community after the formation of the Pelalawan Regency government. (3) This is to determine the working conditions of the fishing community after the formation of the Pelalawan Regency government. (4) This is to determine the condition of the income of the fishermen family of the fishermen community after the formation of the Pelalawan Regency government. The method used in this research is qualitative research methods. The results of the research: Traditional Fishermen in Kuala Terusan Village are classified as below, this is due to the lack of supporting factors such as the lack of education, health and access facilities in Kuala Terusan Village. So that it hinders the economic changes of the fishing community, the socio-economic changes after the formation of the Pelalawan Regency government, namely the opening of access to the village make it easier for the fishing community to expand the place to sell their catch and the community can also access education and health facilities that do not exist in the village. Key Words: Conditions, Social, Economy